Desain Sambungan Menggunakan Link Slab Untuk Jembatan Gelagar Beton Pratekan - Lestari, Tika Ayu Triana; Sebayang, Surya; Purwanto, Eddy (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
In Indonesia, bridges normally use a simply-supported system or a multisimple-span system withexpansion joint. Several problem occurred due to the use of expansion joints in bridge, iecorrosion problem on girders and supports due to rainwater intrusion, users discomfort, high costmaintenance, as well as reduction in bridge lifetime as well. In the design, the existing expansionjoints in the bridges were replaced by using continuous slab construction with link slab system.Design of link slab use classic method by Caner and Zia 1998. The design was conducted on theprestress bridges with length of span 2 x 50 m. The loadings adopted for the design referred to the1725 2016 SNI standard and dimension of girder from WIKA Beton standard. From design werefound that length of link slab zone of 7,55 m and length of debonding zone of 5,05 m. The rotationgained by 0,0058 caused by the truck load. The link slab used reinforcment stool bar D16-125 mmfor the main reinforcement and D12-300 mm for shrinkage-temperature reinforcement. It isexpected that link slab analysis can then use more variable beam types and span lengths.Keyword: Prestress bridge, Link Slab, Expansion Joint